2008
DOI: 10.11646/zootaxa.1728.1.1
|View full text |Cite
|
Sign up to set email alerts
|

A review of the endemic Hawaiian Drosophilidae and their host plants

Abstract: The Hawaiian Drosophilidae is one of the best examples of rapid speciation in nature. Nearly 1,000 species of endemic drosophilids have evolved in situ in Hawaii since a single colonist arrived over 25 million years ago. A number of mechanisms, including ecological adaptation, sexual selection, and geographic isolation, have been proposed to explain the evolution of this hyperdiverse group of species. Here, we examine the known ecological associations of 326 species of endemic Hawaiian Drosophilidae in light o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(108 citation statements)
references
References 23 publications
2
104
2
Order By: Relevance
“…The larval breeding substrate for the majority of the trapped endemic species is decaying leaves of Cheirodendron trigynum (Gaud.) (Araliaceae) (Magnacca et al 2008). Trapping at 57 other endemic forest sites on Hawaii and Maui islands has shown that at least the common species of most of the other endemic groups (haleakalae, picture wings, Nudidrosophila, split tarsus, ciliated tarsus, bristle tarsus, modiÞed mouthparts, and the genus Scaptomyza) are also attracted to BioLure (L.L., unpublished data).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The larval breeding substrate for the majority of the trapped endemic species is decaying leaves of Cheirodendron trigynum (Gaud.) (Araliaceae) (Magnacca et al 2008). Trapping at 57 other endemic forest sites on Hawaii and Maui islands has shown that at least the common species of most of the other endemic groups (haleakalae, picture wings, Nudidrosophila, split tarsus, ciliated tarsus, bristle tarsus, modiÞed mouthparts, and the genus Scaptomyza) are also attracted to BioLure (L.L., unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…They were slightly more common at the highest (1,138 m) location (0.031 Ϯ 0.011 SEM per trap per day) than the three other locations (0.012 Ϯ 0.004). The catches mainly consisted of three Drosophila species in the haleakalae group, whose larvae breed on fungus (Magnacca et al 2008), but also included nine species of Scaptomyza trapped in very small numbers (3.4 specimens per species). Most of these endemic species were common in the Maui endemic forest traps (L.L., unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…Data on substrate type (fungi, leaves, bark or stem, fruit, sap flux) and host plant (fungi, Araliaceae, Campanulaceae, ferns, Nyctagenaceae, Amaranthaceae, Sapindaceae, Fabaceae, Myrsinaceae, Aquifoliaceae and other) were entered based on Magnacca, Foote, and O'Grady (2008). When multiple records existed, we selected those with multiple rearings or multiple offspring.…”
Section: Character Mappingmentioning
confidence: 99%
“…While Araliaceae and Campanulaceae are the most commonly used host plant families (Magnacca, Foote, & O'Grady, 2008), switches between host plant families occurs more frequently, with many shifts occurring within a given species group or even species subgroup (Fig. 2B).…”
Section: The Evolution Of Host Usementioning
confidence: 99%
“…For example larvae of some Scaptomyza species are animal predators. Larvae of species in the subgenus Titanochaeta were reared from thomisid spider egg sacs (Hardy, 1965), and some species in the subgenus Elmomyza feed on insects (Magnacca, et al, 2008). The subgenus Scaptomyza is an herbivorous lineage whose larvae are leaf-miners of mustards (Brassicaceae) and other plant families (Hackman, 1959; Wheeler and Takada, 1966; Maca, 1972; Brncic, 1983; Whiteman, et al, 2011), including the genetic reference plant, Arabidopsis thaliana (Chittenden, 1902).…”
Section: Introductionmentioning
confidence: 99%